Biomass-derived nitrogen-doped hierarchically porous carbon networks as efficient absorbents for phenol removal from wastewater over a wide pH range. Issue 74 (3rd October 2017) - Du, Wenyi; Sun, Junting; Zan, Yongxi; Zhang, Zhengping; Ji, Jing; Dou, Meiling; Wang, Feng
Abstract : Biomass-derived nitrogen-doped hierarchically porous carbon adsorbent was synthesized and exhibited an excellent adsorption performance for phenol removal. Abstract : Developing cost-effective porous carbon adsorbents with large adsorption capacity and superior recyclability over a wide pH range is critical for the efficient removal of toxic phenol from industrial wastewater. Herein, we demonstrate a facile and effective strategy for synthesis of a nitrogen-doped hierarchically porous carbon (NHPC) network derived from cattle bone as a highly efficient adsorbent for the removal of phenol from wastewater. The as-prepared NHPC possessed a high specific surface area (2687 m 2 g −1 ), a unique three-dimensional (3D) hierarchical porous structure and high content of nitrogen doping (2.31 at%). As a result, NHPC exhibited a remarkable adsorption performance towards phenol with a significantly large adsorption capacity of 431 mg g −1 (3.56-fold that of the commercial adsorbent (Norit CGP)), a high adsorption rate of 4.57 g mg −1 h −1 (17-fold that of Norit CGP) and an outstanding recyclability with 98% of the initial adsorption capacity maintained after 5 cycles (75% for Norit CGP). More importantly, the NHPC held almost the identical maximum adsorption capacity over a wide pH range of 2–9, showing a good applicability in the removal of phenol from a variety of wastewaters. Thermodynamic and kinetics analyses indicated that the adsorption process was spontaneous and exothermic, which fitted well the Langmuir isotherm model and pseudo-second-order model. This biomass-based porous carbon with well-defined hierarchical porosity can be applied as a promising adsorbent for efficient removal of phenol from wastewater.